Phenylalanine-derived β-lactam TRPM8 antagonists: revisiting configuration and new benzoyl derivatives - Cristina Martín-Escura; Maria Angeles Bonache; Alicia Medina-Peris; Thomas Voets; Antonio Ferrer-Montiel; Asia Fernández-Carvajal; Rosario González-Muñiz (Exploration of Drug Science)
Aim: To expand the understanding of the structure-activity relationship within a family of amino acid-derived β-lactam TRPM8 (transient receptor potential melastatin channel, subtype 8) antagonists, this work investigated both the configuration-dependence of potency and selectivity, and explored strategies for increasing total polar surface area (TPSA). Methods: Diastereoisomeric compounds derived from H-Phe-OtBu, and analogues incorporating differently substituted benzoyl groups, were synthesized by stereoselective solution pathways. Ca2+ microfluorometry assays were used for TRPM8 antagonist activity assessment, and then confirmed through electrophysiology (patch-clamp assay). The pharmacological activity in vivo was studied on a mice model of oxaliplatin-induced peripheral neuropathy. Results: For OtBu derivatives, a 3S,4S-configuration was preferred, while compounds with 2'R chiral centers show higher selectivity for TRPM8 versus transient receptor potential vanilloid, subtype 1 (TRPV1) than their 2'S-counterparts. N-terminal benzoyl derivatives, which increased TPSA values, resulted in equipotent compounds as previous prototypes, but also showed activity in other pain-related targets [TRPV1 and cannabinoid receptor, subtype 2 (CB2R)]. A selected N-benzoyl derivative displays antinociceptive activity in vivo. Conclusions: The potency and selectivity of these β-lactam TRPM8 antagonists developed from amino acid derivatives depend not only on the configuration but also on the substituents at the 4-carboxy and at the N-benzoyl groups. Dual and multitarget compounds were discovered within this family of TRPM8 antagonists.